The spectrum of Spinal Cord Tumours in a Tertiary Care Centre withEmphasis on Rare Tumours: An Observational Study - Mudita Sharma; Dr. Surabhi Tyagi; Dr.Jyoti Pandey; Dr. B.S. Sharma; Dr. Anubha Choudhary (Tropical Journal of Pathology and Microbiology, 2022)
Introduction: Spinal cord tumour is an abnormal mass of tissue within/or surrounding spinal cord&/or spinal column. They are referred to according to vertebral levels and area in which they arelocated within the spine - Extradural & Intradural (Extramedullary & Intramedullary).Aims andObjectives: To integrate histopathological spectrum of spinal cord tumours with their relevantimmunohistochemistry, their incidence and spectrum about spinal levels, location within spine, ageand sex.Materials and Methods: Hospital-based observational study in Department of Pathology,Mahatma Gandhi Medical College, Jaipur, for two years & includes 70 cases of spinal cord tumours.Results: In our study, 70 cases of spinal cord tumours showed 14 tumour types. Peak incidence wasseen in 61-70 years followed by 41-50 years and lowest in children ˂ 10 years. Male preponderancewas seen. The major histological type was meningiomas 17 cases (24.3%) followed byschwannomas 12 cases (17.14 %) and metastasis in 8 cases (11.4%). In relation to anatomical sitein spinal cord, tumours were most common in the thoracic spine (48.6%) followed by the cervicalspine (15.7 %).Conclusion: In our study, the spectrum of spinal cord tumours is exhibited in 14tumour types. Peak incidence was seen in sixth decade with male preponderance and propensity forthe thoracic segment of the spine. The most common tumour type was meningiomas followed byschwannomas. IHC plays a vital role in accurate diagnosis that helps in recognizing tumourhistogenesis, clinical & radiological correlation, its pathological course, treatment & prognosis. MIB-1assesses grade & aggressiveness of tumour thus helping in evaluating its chances of recurrence.